Perceived threat and coping strategies towards COVID- 19 among Malaysian nurses - Pasi, Hafizah (Japan International Cultural Exchange Foundation, 2022)
Perceived threat is recognised as one of the individual's cognitive assessments toward the likelihood of a danger affecting them and how bad it will be if it does. Additionally, coping strategies are a specific effort, that people employ to master, tolerate, reduce or minimize stressful events. Due to the massive impact of the recent COVID-19 global pandemic, this study aims to explore the perceived threat and coping strategies adopted by Malaysian nurses in facing COVID-19 infections. A cross-sectional study was conducted through an online form involving 319 randomly selected nurses from a teaching hospital on the east coast of Pahang, Malaysia. The perceived threat was measured using the 5-item Brief Illness questionnaire (BIPQ5), while the coping mechanism was measured using the Brief-COPE (Coping Orientation to Problems Experienced) questionnaire. Univariate and multiple linear regression was applied to assess the association between perceived threats and coping strategies adopted toward COVID-19. Perceived threat under the domain of timeliness has the highest mean score of 7.4 ± 2.1 while the lowest was under the domain of identity with a score of 4.8 ± 2.6. For coping strategies, acceptance is the most adopted strategy with a mean score of 5.7 ± 1.4 while religion is the least adopted strategy with a score of 3.5 ± 1.4. Multiple linear regression showed significant positive correlations between the perceived threat of consequences, timeliness and emotional domain with coping strategies by denial, emotional support, instrumental support, behavioural disengagement and religion among the respondents. This study showed that there is a significant positive correlation between perceived threat towards COVID-19 with coping strategies adopted by nurses in this study with timeliness being perceived as the highest threat and acceptance being the coping strategy used most by them. Therefore, any intervention activities focusing on COVID-19 which targeted this population should take into consideration of the factors mentioned to ensure its effectiveness.